2021
DOI: 10.1002/adfm.202101847
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Tilting in Nematic Liquid Crystals Driven by Self‐Assembly

Abstract: Self‐assembly is one of the crucial mechanisms allowing the design multifunctional materials. Soft hybrid materials contain components of different natures and exhibit competitive interactions which drive self‐organization into structures of a particular function. Here a novel type of a magnetic hybrid material where the molecular tilt can be manipulated through a delicate balance between the topologically‐assisted colloidal self‐assembly of magnetic nanoparticles and the anisotropic molecular interactions in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Dendrimers are a group of molecules with branched, ordered, and compact structures. They are synthetically tunable scaffolds for adding various functionalities. When serving as ligands, their conical structure can be nicely fitted onto the NP surface and form a well-surrounded capping layer, preventing NPs from self-aggregating or being negatively influenced by external disturbance, which is very important for NPs with problems in colloidal stability. ,,, Previous studies have shown that using dendritic promesogenic ligands on CoFe 2 O 4 NPs could help suspend magnetic NPs in 5CB, which is of great difficulty due to the magnetic interaction from the NPs themselves. , Besides achieving miscibility at room temperature, it is also critical to maintain the quality of NPs in thermotropic LCs under elevated temperatures; otherwise, aggregation and fusion of NPs during the heating and cooling cycles could bring difficulty in interpreting the data and reproducing the results. However, the mesophases of many LCs are quite above room temperature (Figure ), whereas the performance and stability of NPs are usually very temperature sensitive, bringing more challenges to prepare a uniform and stable LC-NP hybrid system.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers are a group of molecules with branched, ordered, and compact structures. They are synthetically tunable scaffolds for adding various functionalities. When serving as ligands, their conical structure can be nicely fitted onto the NP surface and form a well-surrounded capping layer, preventing NPs from self-aggregating or being negatively influenced by external disturbance, which is very important for NPs with problems in colloidal stability. ,,, Previous studies have shown that using dendritic promesogenic ligands on CoFe 2 O 4 NPs could help suspend magnetic NPs in 5CB, which is of great difficulty due to the magnetic interaction from the NPs themselves. , Besides achieving miscibility at room temperature, it is also critical to maintain the quality of NPs in thermotropic LCs under elevated temperatures; otherwise, aggregation and fusion of NPs during the heating and cooling cycles could bring difficulty in interpreting the data and reproducing the results. However, the mesophases of many LCs are quite above room temperature (Figure ), whereas the performance and stability of NPs are usually very temperature sensitive, bringing more challenges to prepare a uniform and stable LC-NP hybrid system.…”
Section: Introductionmentioning
confidence: 99%
“…This concept can be applied, e.g., to synthesize magneto-responsive nematic liquid crystals. 4 Typical life science applications, on the other hand, include biosensors, 5 magnetic resonance 6 and particle imaging, 7 remote cell control, 8 magnetic drug targeting and delivery, 9 as well as magnetic separation 10 . For each purpose the particle properties need to be optimized: whereas some applications may need superparamagnetic particles (e.g., magnetic resonance imaging), others prefer large particle moments (e.g., biosensors and magnetic separation).…”
Section: Introductionmentioning
confidence: 99%
“…The organic surfactant, which prevents aggregation, can cause another contribution to the shift of the isotropic to nematic phase transition temperature, with increasing particle concentration. Many experimental results have been reported [ 18 , 22 , 23 , 24 ] and theoretical studies performed [ 25 , 26 , 27 ] about the decrease in threshold magnetic field observed in NLCs doped with magnetic nanoparticles, however, it was shown that an increase in the threshold of magnetic fields can also occur [ 28 , 29 ]. As such, the influence of nanoparticles on NLC compound properties depends on their particularities, which are related to their material, size, shape, concentration, etc.…”
Section: Introductionmentioning
confidence: 99%